1994
DOI: 10.1063/1.358310
|View full text |Cite
|
Sign up to set email alerts
|

Giant magneto-impedance and magneto-inductive effects in amorphous alloys (invited)

Abstract: Recent experiments have discovered giant and sensitive magneto-impedance and magneto-inductive effects in FeCoSiB amorphous wires. These effects include a sensitive change in an ac wire voltage with the application of a small dc longitudinal magnetic field. At low frequencies (1–10 kHz) the inductive voltage drops by 50% for a field of 2 Oe (25%/Oe) reflecting a strong field dependence of the circumferential permeability. At higher frequencies (0.1–10 MHz) when the skin effect is essential, the amplitude of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
194
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(199 citation statements)
references
References 15 publications
4
194
0
1
Order By: Relevance
“…Similar peak phenomenon was observed in the uniform wires, ribbons and films, which was attributed to the existence of circumferential or transverse anisotropy and the permeability peak around anisotropy field H K (H K % H P ). [3][4][5][6][7][8] It has been found that in the electrodeposited CoP film there is a transition of magnetic anisotropy with regards to the thickness D of CoP: For D < 0:4 mm, the anisotropy is planar. For 0:4 mm < D < 10 mm it is an oblique anisotropy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar peak phenomenon was observed in the uniform wires, ribbons and films, which was attributed to the existence of circumferential or transverse anisotropy and the permeability peak around anisotropy field H K (H K % H P ). [3][4][5][6][7][8] It has been found that in the electrodeposited CoP film there is a transition of magnetic anisotropy with regards to the thickness D of CoP: For D < 0:4 mm, the anisotropy is planar. For 0:4 mm < D < 10 mm it is an oblique anisotropy.…”
Section: Resultsmentioning
confidence: 99%
“…1,2) The GMI effect consists in a magnetic field induced changes in the complex impedance due to the variation of magnetic permeability. Besides of the uniform wires, ribbons and films, [3][4][5][6][7][8] this effect has been observed in inhomogeneous structured materials such as non -magnetic conducting wire plated with magnetic layers and some sandwich films. [9][10][11][12][13][14][15][16][17][18] Large GMI effect occurs at a relative low frequency in BeCu/NiFe, 9) BeCu/CoFeNi, 10) Ag/NiFe 11) and Cu/CoP 12,13) plated wires.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] This effect includes a sensitive change in impedance with application of a small dc magnetic field. It has been widely accepted that the magnetoimpedance is strongly correlated with the variation of the penetration depth via the permeability.…”
Section: Introductionmentioning
confidence: 99%
“…The giant magneto-impedance (GMI) effect of these wires which used for weak-field detection and high-resolution sensors has been attracted much attentions [1][2][3] . Many previous works focused on annealing treatment for improving the GMI ratio and field response sensitivity of the microwires simultaneously by releasing the residual inner stress of an as-quenched microwire which enhances the circumferential permeability μ φ , such as joule heat-treatment and stress annealing [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%